Biopsychosocial and Economic Determinants of Condom Use among Gay in Tulungagung District, East Java - Fransisca Novalia Permana; Argyo Demartoto; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2017)
Background: HIV/ AIDS epidemics emerged among men who have sex with men, particularly among gay, due to unsafe anal sex practice. As studies have shown having sex without condom increases the risk of HIV/ AIDS 18 times as many as per-vaginal sex. This study aimed to examine biopsychosocial and economic determinants of condom use among gay in Tulungagung district, East Java.Subjects dan Method: This was an analytic observational study using cross-sectional design. The study was conducted in Tulungagung district, East Java, from January to February 2017. A sample of 165 gays was selected by random sampling out of all 300 gays in the community. The independent variables were perceived susceptibility, perceived seriousness, perceived benefit, perceived barrier, and self- efficacy. The dependent variable was condom use. The data were collected by a set of pre-tested questionnaire, and analyzed by multiple logistic regression.Results: Perceived seriousness (OR=2.83; 95% CI=1.14 to 7.04; p=0.025), perceived benefit (OR= 4.90; 95% CI=2.11 to 11.36; p<0.001), self-efficacy (OR=4.48; 95% CI=2.03 to 9.89; p<0.001), increased the likelihood of condom use. Perceived susceptibility (OR= 1.02; 95% CI=0.40 to 2.59; p=0.972) increased the likelihood of condom use, although it was not statistically significant. Perceived barrier (OR= 0.36; 95% CI=0.13 to 1.00; p=0.050) decreased the likelihood of condom use, and it was statistically significant.Conclusion: Perceived seriousness, perceived benefit, and self- efficacy, increased the likelihood of condom use among gay. Perceived barrier decreased the likelihood of condom use.Keywords: biopsychosocial, determinant, condom use, HIV/ AIDS, GayCorrespondence: Fransisca Novalia Permana. Masters Program in Public Health, Sebelas Maret University, Surakarta. Email: fransisca2713@gmail.com. Mobile: +6285645762007.Journal of Health Promotion and Behavior (2017), 2(1): 88-97https://doi.org/10.26911/thejhpb.2017.02.01.08